ETHICAL CONCERNS REGARDING COMMERCIALIZATION OF DEEP BRAIN STIMULATION FOR OBSESSIVE COMPULSIVE DISORDER - Erickson-Davis, Cordelia (Bioethics, 2012)
The United States Food and Drug Administration's recent approval of the commercial use of Deep Brain Stimulation (DBS) as a treatment for Obsessive Compulsive Disorder (OCD) will be discussed within the context of the existing USA regulatory framework. The purpose will be to illustrate the current lack of regulation and oversight of the DBS market, which has resulted in the violation of basic ethical norms. The discussion will focus on: 1) the lack of available evidence on procedural safety and efficacy, 2) the numerous conflicts of interest held by research investigators, and 3) the ambiguity of both aforementioned categories due to an inherent lack of transparency in the research. It is argued that in order to address these issues, ethical analyses of DBS for psychiatric disorders must include the role of the industry forces that have become the primary impetus for this research. As such, DBS for OCD serves as an important case example in studies of neurotechnology and innovative surgery.